Post-Traumatic Stress Disorder among Medical Support Staff in Bangladesh During the Covid-19 Pandemic (Journal of Preventive and Social Medicine, 2026)
Background: The healthcare professionals, especially the medical support staff, suffered a huge physical as well as psychological trauma during the COVID-19 pandemic. By recognizing their role as frontline workers, they were the most exposed group who faced the terrifying virus, which created mental health problems during the pandemic. The purpose of this study is to find the prevalence of PTSD among medical support staff during the COVID-19 pandemic.Methods: This cross-sectional study was designed to assess the prevalence of post-traumatic stress disorder (PTSD) among purposefully selected 289 medical support staff working at treating COVID-19 patients in government hospitals during the COVID-19 pandemic in Bangladesh. The Impact of Event Scale-Revised (IES-r) was used to prepare the questionnaire.Results: The mean age of the medical support staff was 31.09±8.91 years. All of them suffered from mild to severe types of PTSD. Most of the participants were male (65.7%), aged between 26 to 35 years (46.7%), married (70.6%), working indoors (64.4%), and living with family (73.4%). 65.1% of the participants didn’t have any co-morbidities, 12.1% of the participants were suffering from hypertension, 11.4% of them were suffering from asthma/copd, 8.0% were suffering from diabetes, and the rest of them were suffering from other chronic diseases. This study also found that about two-thirds of the participants (181) were suffering from mild PTSD.Conclusion: Appropriate measures were urgent to make the frontliner health care support staff’s mental health conditions recognized and well-treated, as well as for prevention.JOPSOM 2025; 44(1): 45-53